2022
DOI: 10.3390/microorganisms10051067
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Campylobacter spp. Isolated from Broiler Chicken Meat and Human Patients in Estonia

Abstract: Poultry meat is considered the most important source of Campylobacter spp. Because of rising antimicrobial resistance in Campylobacter spp., this study investigated the antimicrobial resistance of Campylobacter isolates from fresh broiler chicken meat originating from the Baltic countries sold in Estonian retail settings. Additionally, human clinical isolates obtained from patients with Campylobacter enteritis in Estonia were analysed. The aim of this study was to investigate the susceptibility of Campylobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…in EU member states. In particular, both C. jejuni and C. coli from poultry sources in the EU exhibited high resistance against (fluoro-)quinolones and tetracycline, which is in line with our data [ 6 , 23 , 24 ]. However, notably, the resistance rate to ciprofloxacin and tetracycline was 100% in isolates from industrial poultry samples in Georgia, while in backyard chicken and in human isolates Campylobacter strains displayed slightly lower resistance against both antimicrobials.…”
Section: Discussionsupporting
confidence: 92%
“…in EU member states. In particular, both C. jejuni and C. coli from poultry sources in the EU exhibited high resistance against (fluoro-)quinolones and tetracycline, which is in line with our data [ 6 , 23 , 24 ]. However, notably, the resistance rate to ciprofloxacin and tetracycline was 100% in isolates from industrial poultry samples in Georgia, while in backyard chicken and in human isolates Campylobacter strains displayed slightly lower resistance against both antimicrobials.…”
Section: Discussionsupporting
confidence: 92%
“…McGill et al [52] found similar resistance prevalence to erythromycin, ciprofloxacin, and tetracycline between food and human isolates in Ireland from 2001 to 2002. Similarly, in Estonia, Tedersoo et al [53] found a comparable resistance to antibiotics for broiler chicken meat collected between 2018 and 2019 and human Campylobacter isolates. The appearance of resistant Campylobacter isolates in humans and animals likely reflects the wide use of antibiotics in poultry production.…”
Section: Discussionmentioning
confidence: 88%
“…For example, Denmark has restricted the use of carbapenems, fluoroquinolones and colistin. In Sweden, only isolated outbreaks of the use of antibiotics in production are known (Tedersoo et al, 2022)…”
Section: Advances Inmentioning
confidence: 99%